2020
DOI: 10.1021/acsbiomaterials.0c01437
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenol-Assisted Chemical Crosslinking: A New Strategy to Achieve Highly Crosslinked, Antioxidative, and Antibacterial Ultrahigh-Molecular-Weight Polyethylene for Total Joint Replacement

Abstract: Highly crosslinked ultrahigh-molecular-weight polyethylene (UHMWPE) bearings are wear-resistant to reduce aseptic loosening but are susceptible to oxidize in vivo/in vitro, as reported in clinical studies. Despite widespread acceptance of antioxidants in preventing oxidation, the crosslinking efficiency of UHMWPE is severely impacted by antioxidants, the use of which was trapped in a trace amount. Herein, we proposed a new strategy of polyphenol-assisted chemical crosslinking to facilitate the formation of a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…1,2 Specifically, the excessive accumulation of reactive oxygen species (ROS) in infected wounds impairs the antioxidant defense system, induces a strong inflammatory response to facilitate disease progression, restricts angiogenesis, and slows wound tissue regeneration. 3,4 Recently, it has been demonstrated that ROSscavenging biomaterials exhibit an enhanced therapeutic effect for wound healing, including nonsteroidal anti-inflammatory drugs, 5 polyphenols, 6 artificial nanozymes (e.g., fullerene, MoS 2 ), 7 and others. Among them, dopamine-containing materials with numerous catechol groups on the surface have been paid much attention to act as promising ROS scavengers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Specifically, the excessive accumulation of reactive oxygen species (ROS) in infected wounds impairs the antioxidant defense system, induces a strong inflammatory response to facilitate disease progression, restricts angiogenesis, and slows wound tissue regeneration. 3,4 Recently, it has been demonstrated that ROSscavenging biomaterials exhibit an enhanced therapeutic effect for wound healing, including nonsteroidal anti-inflammatory drugs, 5 polyphenols, 6 artificial nanozymes (e.g., fullerene, MoS 2 ), 7 and others. Among them, dopamine-containing materials with numerous catechol groups on the surface have been paid much attention to act as promising ROS scavengers.…”
Section: Introductionmentioning
confidence: 99%
“…A wound infection occurs when pathogenic organisms invade viable tissue surrounding the wound, which causes inflammation by triggering the body’s immune response and leads to tissue damage and a slowly healing process. , Specifically, the excessive accumulation of reactive oxygen species (ROS) in infected wounds impairs the antioxidant defense system, induces a strong inflammatory response to facilitate disease progression, restricts angiogenesis, and slows wound tissue regeneration. , Recently, it has been demonstrated that ROS-scavenging biomaterials exhibit an enhanced therapeutic effect for wound healing, including nonsteroidal anti-inflammatory drugs, polyphenols, artificial nanozymes (e.g., fullerene, MoS 2 ), and others. Among them, dopamine-containing materials with numerous catechol groups on the surface have been paid much attention to act as promising ROS scavengers. , The catechol groups endow dopamine with the antioxidant capability to scavenge ROS in a dose-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…Xu's group recently proposed a novel strategy of polyphenol-assisted chemical crosslinking to obtain antioxidative and antibacterial properties, based on the crosslinking sites formation by multiple reactive phenolic hydroxyl groups of EGCG coupling with the nearby free radicals. 68 When the concentration of EGCG was 4 wt%, the resulting composites exhibited high sterilizing efficiencies of 92% and 97% for Gram-negative Escherichia coli ( E. coli ) and Gram-positive Staphylococcus aureus ( S. aureus ), respectively. Especially, the sterilizing efficiencies were further enhanced to ∼100% when the concentration of EGCG was above 6 wt%.…”
Section: Natural Polyphenols In Multifunctional Compositesmentioning
confidence: 99%
“…The strong radical-scavenging activity of tea polyphenols (C) is ascribed to the presence of the phenolic groups which can generate quininine [ 34 ]. Furthermore, due to the chemical reactivity of the hydroxyl groups on aromatic rings, the tea polyphenols (C) are capable to form both noncovalent and covalent bonds [ 35 , 36 , 37 ]. Shin et al [ 35 ] reviewed the use of pyrogallol-containing polyphenols as molecular glues in biomolecular interactions, modifiers in material-independent surface chemistry, and chemical moieties to form covalent linkages in biomaterials.…”
Section: Introductionmentioning
confidence: 99%
“…Shin et al [ 35 ] reviewed the use of pyrogallol-containing polyphenols as molecular glues in biomolecular interactions, modifiers in material-independent surface chemistry, and chemical moieties to form covalent linkages in biomaterials. Ren et al [ 37 ] prepared a highly crosslinked ultrahigh-molecular-weight polyethylene with the assistance of polyphenol. The reactive phenolic hydroxyl groups of the tea polyphenol coupled with free radicals and formed extra crosslinking sites.…”
Section: Introductionmentioning
confidence: 99%